PERENCANAAN PENGOMPOSAN SEBAGAI ALTERNATIF PENGOLAHAN SAMPAH ORGANIK (STUDI KASUS: TPA PUTRI CEMPO – MOJOSONGO) - Budisulistiorini, Sri Hapsari; Sutrisno, Endro; Sinaga, August (Universitas Diponegoro, 2010)
Garbage management system in many cities in Indonesia is only transporting the garbage from their sources to the solid waste landfill without existence of furthermore processing which can lessen the danger which possible can be happened. Therefore, one of the correct processing method is recycle by composting, because 50 - 80 % city garbage represent the organic garbage that can be composted. Besides useful to lessen the amount arise the organic garbage, composting also give the advantage to all farmer, as well as assigning value economic for organic garbage. Surakarta City, that have density of population have composition of organic garbage of 70,05 % from the garbage entering the landfill, or equal to 808,51 m3/day. From arising the organic garbage, the land requirement for the composting facility is equal to 1,5 Ha with the compost production is 7.326,05 ton/year. Compost facility in TPA Putri Cempo consisted of garbage input site, activated compost site, filtering site, storage and offices. The cost needed to make this composting facility were Rp 8.937.486.128